The MuPix high voltage monolithic active pixel sensor for the Mu3e experiment - Augustin, Heiko; Förster, Fabian; Herkert, Adrian; Huang, Qinhua; Huth, Lennart; Kiehn, Moritz; Kozlinskiy, Alexandr; Philipp, Raphael; Schöning, André; Shrestha, Shruti; Bruch, Dorothea vom; Wiedner, Dirk (Journal of Instrumentation, 2015)
Mu3e is a novel experiment searching for charged lepton flavor violation in the rare decay μ → eee. In order to reduce background by up to 16 orders of magnitude, decay vertex position, decay time and particle momenta have to be measured precisely. A pixel tracker based on 50 μm thin high voltage monolithic active pixel sensors (HV-MAPS) in a magnetic field will deliver precise vertex and momentum information. Test beam results like an excellent efficiency of >99.5% and a time resolution of better than 16.6 ns obtained with the MuPix HV-MAPS chip developed for the Mu3e pixel tracker are presented.